Superparamagnetic iron oxide‐enhanced magnetic resonance imaging is useful in predicting malignant potential of vascular transformation of hypointense hypovascular nodules on gadoxetic acid‐enhanced magnetic resonance imaging. Issue 11 (21st February 2017) - Tanaka, Yoshiaki; Nakazawa, Takahide; Inoue, Tomoyoshi; Yamane, Keiko; Kubota, Kousuke; Uojima, Haruki; Takada, Juichi; Okuwaki, Yusuke; Hidaka, Hisashi; Shibuya, Akitaka; Kokubu, Shigehiro; Matsunaga, Keiji; et al.
Abstract : Aim: To examine whether superparamagnetic iron oxide (SPIO)‐enhanced magnetic resonance imaging (MRI) can be used to assess the malignant potential of hepatic hypovascular nodules showing hypointensity during the hepatobiliary phase (HBP) on gadoxetic acid (Gd–EOB–DTPA)‐enhanced MRI. Methods: The study included 42 patients with chronic liver disease who had small hypovascular nodules (5–15 mm) showing hypointensity during the HBP on Gd–EOB–DTPA‐enhanced MRI. The SPIO‐enhanced T2‐weighted MRI analyzed whether the signal intensity of each nodule was high. Nodules were prospectively followed up until hypervascularization by periodic Gd–EOB–DTPA‐enhanced MRI. Initial MRI findings and clinical variables were used to analyze predictive factors for hypervascularization. Results: We analyzed 77 nodules, of which 19 (25%) showed hypervascularization during the observation period. The cumulative rates for hypervascularization were 11% and 22% at 1 and 2 years, respectively. Hyperintensity was observed in 12 nodules (16%) on SPIO‐enhanced T2‐weighted MRI; among these, 7 (58%) showed hypervascularization, whereas 12 (18%) of the remaining 65 nodules without hyperintensity showed hypervascularization ( P  = 0.007). A Cox model revealed that independent predictors of hypervascularization included hyperintense nodules on SPIO‐enhanced MRI ( P  < 0.001). The cumulative rates for hypervascularization in hyperintense nodules on SPIO‐enhanced MRI were 52% at 1 year, whereas these rates were 3% for non‐hyperintense nodules. Conclusion: Superparamagnetic iron oxide‐enhanced MRI is useful for predicting the malignant potential of vascular transformation of hypovascular nodules with hypointensity observed in the HBP on Gd–EOB–DTPA‐enhanced MRI.